Біолістична трансформація незрілих зародків кукурудзи - Нітовська, І.О.; Абраїмова, О.Є.; Сатарова, Т.М.; Шаховський, А.М.; Моргун, Б.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. Maize (Zea mays L.) is one of the most economically important crops which were considerably improved by modern biotechnology. For efficient production of transgenic maize, immature embryos and two transformation techniques for transgenes delivery (Agrobacterium-mediated transformation and particle bombardment) were employed. However, genetic transformation is genotype dependent and is not routine procedure. Thus, the aim of the current studies was to carry out the biolistic transformation of immature maize embryos for commercial genotypes propagated in fields, and to prove their competence for genetic transformation. Methods. Particle bombardment of immature maize embryos for 21 commercial genotypes using pAHC25 vector was carried out. Histochemical analysis of the phosphinothricin resistant plant material for the presence of β-glucuronidase was performed. Plant DNA was analyzed for the presence of bar gene by PCR method. Results. Following particle bombardment, phosphinothricin resistant calli and plant regenerants were obtained. Histochemical analysis showed the presence of β-glucuronidase in the obtained plant material. PCR analysis proved the presence of bar gene in plant DNA of the phosphinothricin resistant calli and 6 regenerant lines. Out of 21 maize genotypes, inbred line PLS61 and hybrids F₁ PLS61♀×ДК744♂, PLS61♀×ДК304♂, and ДК959♀×PLS61♂ were the most competent for biolistic transformation. Conclusions. After biolistic transformation of immature maize embryos with pAHC25 vector, phosphinothricin resistant calli and plant regenerant lines containing β-glucuronidase have been obtained. The presence of bar gene detected by PCR method indicated the transgenic nature of the obtained plant material. Four most responsive for the biolistic transformation genotypes were selected from 21 commercial lines and hybrids grown in Ukraine.